The ‘shades of grey’ in research integrity—Researchers admit to questionable research practices that they do not perceive to be serious - Marta Entradas; Yan Feng; Inês Carneiro e Sousa (PLoS ONE, 2026)
Research misconduct practices like fabrication, falsification and plagiarism (FFP) are serious deviations from good research conduct, which have attracted attention in the literature due to the damage they can bring to science and society. However, less is known about the grey zone of researchers’ behaviours that deviate from responsible research conduct but do not fall under serious research misconduct practices. These are known as questionable research practices (QRPs), and they are believed to pose a no less serious threat to research integrity and science. Despite increasing research on the topic, the extent of the problem in different research fields and contexts is unknown. Using a sample of researchers working in Portuguese universities in six main fields of research (n = 1573), we report on QRPs that researchers admit to and how serious they perceive them to be, and on predictors of engagement in QRPs. We find that QRPs are widespread across all fields of research and seniority levels. Yet, younger, more prolific researchers, and those dismissing the seriousness of QRPs admitted to more QRPs. This suggests that some groups are at higher risk of misconduct and that there is a need for studying the motivations behind more susceptible groups to engage in QRPs.